2020
DOI: 10.1097/prs.0000000000006379
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin A Salvage of Ischemic Hand Trauma

Abstract: Summary: Posttraumatic hand injuries from crush injury, infusion, or iatrogenic vascular cannulation can cause ischemic finger damage that can progress to necrosis and digital amputation. Botulinum toxin type A (Botox) improves blood flow in chronic vasospastic disorders of the hand. Botox’s efficacy in salvaging ischemic loss in digits in acute traumatic and iatrogenic injury has not been previously reported. From February of 2015 to December of 2016, 11 patients at a Level I trauma center (West V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Clinicians have achieved good prophylactic results with BTXA injection near the surgical incision after surgery. Laarakker reported that BTXA is used to salvage ischaemic hand injuries to avoid finger or limb amputation 27 . However, some studies show the opposite conclusion with BTXA injection 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have achieved good prophylactic results with BTXA injection near the surgical incision after surgery. Laarakker reported that BTXA is used to salvage ischaemic hand injuries to avoid finger or limb amputation 27 . However, some studies show the opposite conclusion with BTXA injection 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The toxin cleaves the SNARE proteins and indirectly inhibits neurotransmitter release of acetylcholine, but also glutamate, norepinephrine, substance P, and calcitonin gene-related peptide at the synapses and neuromuscular junction. Each neurotransmitter affects vascular tonus resulting in decreased vascular smooth muscle tone leading to vasodilatation [ 8 ]. The clinical effect of Botox® gradually occurs within 3–10 days and lasts approximately 12 weeks.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In the Botox group, all digits were preserved. Moreover, cases experienced pain relief and improvement of digital perfusion [ 8 ]. The physiological mechanisms of Botox® are not fully elucidated.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…We routinely acutely use botulinum A toxin injections in severe traumatic or crush injuries of the hand. Laarakker and Borah described dramatic improvements in digital survival in hand and finger injuries with early Botox injections into the affected fingers and adjacent to radial and ulnar arteries [15]. Botox use for vasospastic disease of the hand is well-described by Neumeister in multiple settings [16].…”
Section: Discussionmentioning
confidence: 99%